Prosthetic complications with dental implants: a bibliometric analysis of 20 top-cited articles - Khan, Farhan Raza; Kazmi, Syed Murtaza Raza; Siddiqui, Humayun Kaleem; Aziz, Ayesha (Journal of the Pakistan Medical Association, 2023)
The purpose of this review was to explore the 20 most cited articles on prosthetic complications with dental implants. Identification of such articles could be helpful in prosthodontics residency programmes in devising the curriculum of essential reading material in implantology. The Institute for Scientific Information, Web of Science Database, and Google Scholar were used to identify the 20 top-cited articles published in journals from 1980 till June 2021. These articles were then evaluated according to the number of citations, authors, study design, publication year, and publishing journal. Descriptive statistics were computed for bibliometrics. It was observed that the citation count ranged from 6,391 to 315 (in descending order). The Toronto study is the most cited study on dental implant prosthetic complications. Prospective studies and systematic and narrative reviews were the predominant study designs used in the articles; however, alarmingly no randomised controlled trials were included in the list.